Revisiting Medicalization: A Critique of the Assumptions of What Counts As Medical Knowledge - Correia, Tiago (Frontiers in Sociology, 2017)
The concept of medicalization is hugely influential and empirical studies have demonstrated that medicalization has largely been achieved through the work of medical professionals or scientists, but also increasingly through the efforts of patients or citizens seeking to legitimize their distress through defining it as a ‘medical’ problem. In this article, I argue that the concept of medicalization is still fundamentally important to the sub-discipline of medical sociology, but that there is a need to revisit and critique its conceptualization. I draw on reflexive arguments within the literature that we, as sociologists, have tended to reproduce the assumptions of the medical profession about what counts as medical knowledge and practice, and on literature that explores the complex and plural ways in which people seek to make sense of their illnesses. I argue that there have been few attempts to engage with the question of how ‘making things medical’ occurs in a global context of medical pluralism. By revisiting Conrad’s approach to defining medicalization, I argue for a separation between empirical observations of the dominance of biomedical knowledge, from theoretical observations about medical knowledge and definitions. I argue for a ‘knowledge-based’ approach to medicalization by opening up the definition of ‘making things medical’ to include all forms of medical knowledge in a global society. The concept of medicalization can then be replaced with medicalizations (plural). To argue this, I take two steps: first, I draw on hermeneutic philosophy to argue that there is a stable definition of medicine on which to base an argument that apparently diverse forms of medical practice can be grouped together and used within the concept of medicalization; second, I argue that medicalization is not unproblematically linked to medical social control. The ‘success’ or not of different attempts to define things as medical problems in part depends on the social and political context. This new approach allows sociologists to make sense theoretically of differences we see in comparative empirical research between whether ‘diseases’ are acknowledged in different national or cultural context. Finally, I provide the readers with guidance on the operationalization of this concept in empirical study.